2019
DOI: 10.1080/08927936.2019.1569908
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Factors and Cognitive Function in Cat Ownership and Attachment in Community-dwelling Older Adults

Abstract: Few studies consider the health benefits of pet ownership from a biopsychosocial perspective, and a paucity of studies investigate cat ownership. The current study was designed to determine if psychosocial factors (stress, loneliness, and depression), biological levels of stress and inflammation (salivary cortisol, interleukin-1␤, and C-reactive protein [CRP]), and cognitive function were associated with companion cat ownership/attachment in community-dwelling older adults. Community-dwelling older adults (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…As is common in animal-related research, women were over-represented in our sample, despite actively encouraging men to participate. This over-representation of women in our study, combined with the following gender differences, show that our results might be less applicable to male cat owners: women have a more positive attitude towards animals [ 111 ], seem to attach more to animals [ 6 , 63 , 112 , 113 ], have more empathy for living beings [ 114 ], and more often attribute traits such as ‘communicative’ and ‘empathetic’ to cats [ 82 ] (this study, results not shown). Third, although participants lived all over the Netherlands, people from the northern part of the country were slightly over-represented.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As is common in animal-related research, women were over-represented in our sample, despite actively encouraging men to participate. This over-representation of women in our study, combined with the following gender differences, show that our results might be less applicable to male cat owners: women have a more positive attitude towards animals [ 111 ], seem to attach more to animals [ 6 , 63 , 112 , 113 ], have more empathy for living beings [ 114 ], and more often attribute traits such as ‘communicative’ and ‘empathetic’ to cats [ 82 ] (this study, results not shown). Third, although participants lived all over the Netherlands, people from the northern part of the country were slightly over-represented.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, owners’ relationship satisfaction and level of attachment were found to be associated with an owner’s social (living) situation [ 25 , 59 , 60 ], gender [ 28 , 61 , 62 ], age [ 28 , 63 ], and educational level [ 28 ]. However, the social function of the cat, and hence the relationship perception of the owner, might not only be associated with characteristics of the owner but also by characteristics of the cat.…”
Section: Introductionmentioning
confidence: 99%
“…While some of the earliest uses of animals to improve the health of people were farm animals, modern studies most often use dogs, then companion horses [70,71,72], and, to a lesser extent, cats [43,73]. Within the last three decades, other species have been used, including fish [23,62,74,75], birds [76], guinea pigs [47], and reptiles [77].…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…Notwithstanding this, some other criteria were hardly met by any study (e.g., sufficient timeframe, exposure(s) assessed more than once over time). All in all, the study quality was satisfactory: one-half of the studies [ 7 , 17 , 21 , 22 , 24 , 39 , 43 48 ] was rated as “good”, the other half [ 18 20 , 23 , 36 38 , 49 53 ] as “fair”.…”
Section: Resultsmentioning
confidence: 99%
“…(If not prospective should be answered as ‘no’, even is exposure predated outcome) (7) Was the timeframe sufficient so that one could reasonably expect to see an association between exposure and outcome if it existed? Antonacopoulos (2010) [ 50 ] Yes Yes Not reported Yes No No (cross-sectional) No (cross-sectional) Antonacopoulos (2017) [ 49 ] Yes Yes Not reported Yes No Yes Yes Bennett (2015) [ 38 ] Yes Yes Not reported Yes No No (cross-sectional) No (cross-sectional) Black (2012) [ 36 ] Yes Yes Yes Yes Yes No (cross-sectional) No (cross-sectional) Branson (2019) [ 43 ] Yes Yes Not reported Yes Yes No (cross-sectional) No (cross-sectional) Carr (2021) [ 22 ] Yes Yes Not reported Yes No No (simultaneously) Yes Carr (2020) [ 44 ] Yes Yes …”
Section: Resultsmentioning
confidence: 99%